Primary osseous chondrosarcoma in the lumbar spine: case report and literature review with analysis - Chih-Hisu Tu (SAGE Publishing, 2021)
Primary spinal chondrosarcoma (CS) is rare. Only a few previous case reports have included a detailed description of the surgical process used to treat the CS. In addition, a paucity of documentation exists comparing differences in the outcomes between the approaches in en bloc resection. Here, we present a case of CS in the lumbar (L) spine treated with two-stage (anterior and posterior approach) en bloc surgery and analyze the differences between one-stage and two-stage approaches in the treatment of primary lumbar CS. A 30-year-old male patient with an L3 vertebral body CS presented with back pain and lower limb weakness. Lumbar spine magnetic resonance imaging (MRI) showed an L3 vertebral body tumor with cord and root compression. Two-stage surgery comprising posterior total laminectomy and transpedicular screw fixation over L2–L4 in the first stage, with subsequent anterior corpectomy, cage implantation, and anterior lumbar interbody fusion was performed to achieve total tumor removal and stabilization. The patient’s symptoms improved postoperatively, with no recurrence as of the 2-year follow-up. The analysis of previous similar cases showed that two-stage surgery, compared with one-stage surgery, appears to be beneficial in lumbar spine multisegment disease, providing a lower recurrence rate.